Infective Endocarditis during Pregnancy—Keep It Safe and Simple! - Viviana Aursulesei Onofrei; Cristina Andreea Adam; Dragos Traian Marius Marcu; Radu Crisan Dabija; Alexandr Ceasovschih; Mihai Constantin; Elena-Daniela Grigorescu; Antoneta Dacia Petroaie; Florin Mitu (Medicina, 2023)
The diagnosis of infective endocarditis (IE) during pregnancy is accompanied by a poor prognosis for both mother and fetus in the absence of prompt management by multidisciplinary teams. We searched the electronic databases of PubMed, MEDLINE and EMBASE for clinical studies addressing the management of infective endocarditis during pregnancy, with the aim of realizing a literature review ranging from risk factors to diagnostic investigations to optimal therapeutic management for mother and fetus alike. The presence of previous cardiovascular pathologies such as rheumatic heart disease, congenital heart disease, prosthetic valves, hemodialysis, intravenous catheters or immunosuppression are the main risk factors predisposing patients to IE during pregnancy. The identification of modern risk factors such as intracardiac devices and intravenous drug administration as well as genetic diagnostic methods such as cell-free deoxyribonucleic acid (DNA) next-generation sequencing require that these cases be addressed in multidisciplinary teams. Guiding treatment to eradicate infection and protect the fetus simultaneously creates challenges for cardiologists and gynecologists alike.